2012
DOI: 10.1051/matecconf/20120101004
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Modeling and Analysis of a Vertical Springless Energy Harvester

Abstract: Abstract. Harvesting energy from ambient sources has attracted the attention of researchers and scientists over the last few decades. While solar, thermal and wind energies have been exploited over the years, a new type of energy that has emerged in recent years, and is the subject of many research projects, is vibration energy harvesting. In this paper we will describe and analyze a recently proposed vibration energy harvester, namely the "Springless" vibration energy harvester. In this study, we will model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Several configurations are possible, with levitation systems [ 21 , 22 ], damping springs [ 23 , 24 ] or high-frequency vibrations [ 25 , 26 ]. Some configurations use springs on top and magnets on the bottom to amplify the damping effect [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several configurations are possible, with levitation systems [ 21 , 22 ], damping springs [ 23 , 24 ] or high-frequency vibrations [ 25 , 26 ]. Some configurations use springs on top and magnets on the bottom to amplify the damping effect [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have shown a substantial increase in computational power and a subsequent decrease in power consumption of small-scale electronics. This has led to increased usage of batterybased mobile electronic devices [1][2][3][4]. However, limited energy densities in batteries hamper widespread adoption of these devices when applications require long lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Harvesters, with linear mechanical oscillators, suffer inherent limitations in terms of narrow bandwidth around the fundamental frequency and limited scalability to match the fundamental frequency to ambient vibration frequency upon device integration [14]. Bandwidth enhancements have been achieved through either smooth nonlinear harvesting [15,16], piecewise (non)linear harvesting [3,17], parametric excitation [18], multimodal harvesting [19,20], or frequency up-conversion [8,21] techniques, resulting in increased robustness to nonstationary vibrations. However, strong dependency on vibration magnitudes [17], aperiodicity of solutions [22] and limited low-frequency power generation [14] still limit the practical application of VEHs.…”
Section: Introductionmentioning
confidence: 99%
“…In [El Aroudi et al, 2013a], this system was reconsidered and its dynamical behavior was studied by time-domain and frequency-domain numerical simulations using long-time integration performed on a continuoustime PWL model. Other studies dealing with PWL systems that can be used as energy harvesters can be found in [Bendame and Abdel-Rahman, 2012], [Soliman et al, 2008] where a prototype of an electromagnetic micro generator is designed and analyzed both numerically and experimentally. PWL switched systems constitute a special class of hybrid systems [Liberzon, 2003] and arise often in practical control systems when some nonlinear components such as switching, dead-zone, saturation, relays, and hysteresis are encountered.…”
Section: Introductionmentioning
confidence: 99%